Quality improvement in surgery: introduction of the American College of Surgeons National Surgical Quality Improvement Program into New South Wales. Issue 5 (9th April 2019) - Richardson, Arthur J.; Cox, Michael R.; Shakeshaft, Anthony J.; Hodge, Bruce; Morgan, Gary; Pang, Tony; Zeng, Mingjuan; Scanlon, Kate; Austin, Robyn; Dawadi, Ashma; Burgess, Crystal; Rawstron, Ellen; et al.
Abstract : Background: Quality improvement in surgery requires accurate, reliable, risk‐adjusted and comparative data. The American College of Surgeons (ACS) National Surgical Quality Improvement Program (NSQIP) takes reliable clinical data and provides risk‐adjusted comparisons with more than 800 hospitals. This paper describes the early outcomes of introducing this programme into New South Wales (NSW). Methods: Four NSW hospitals formed a collaborative. Surgical clinical reviewers were trained and data collected. Risk‐adjusted reports were returned to individual hospitals and the NSW Collaborative. Results: The results identified that the NSW Collaborative were outliers for the following causes of morbidity: urinary tract infections, surgical site infections, pneumonia and 30‐day readmissions. Conclusion: We have shown that ACS‐NSQIP can be adapted to Australia and there is a plan to widen the programme in NSW. Abstract : This is an article setting out the introduction of National Surgical Quality Improvement Program (NSQIP) into New South Wales. There are a large number of authors all of whom have contributed to the project and I would ask that they all be included.